Scalable mechanochemical synthesis of beta-ketoenamine-linked covalent organic frameworks for methane storage - Asokan, Kiran; Patil, Manoj Krishnat; Mukherjee, Shatabdi Porel; Sukumaran, Santhosh Babu; Nandakumar, T. (Chemistry-An Asian Journal, 2022)
In the current scenario of increased pollution and releasing toxic gases by burning petroleum products, switching to natural gas is more promising for reducing CO2 emissions and air pollutants. Hence, research on Liquefied Natural Gas and Compressed Natural Gas is gaining more value. However, natural gas primarily consists of CH4, which has less energy density than conventional fuels. Interestingly, since the C-H ratio of CH4 gas is 1 : 4, it is easily combustible, gives less carbon footprint, and reduces unburnt hydrocarbon pollution. Hence, research on storing and transporting CH4 has utmost importance, and porous materials are one of the suitable candidates for storing CH4. Herein we report the scalable synthesis of highly porous and crystalline covalent organic frameworks for storing CH4 at room temperature and pressure. Two COFs, namely, Tp-Azo and Tp-Azo-BD(Me)(2), synthesized in 1 kg at similar to 45 g batch scale using a Planetary mixer, displayed a maximum BET surface area of around 3345 m(2)/g, and 2342 m(2)/g and CH4 storage of 174.10 cc/cc and 151 cc/cc, respectively. A comparison of the CH4 sorption of Tp-Azo and Tp-Azo-BD(Me)(2) COFs synthesized in different batches has a variation of only +/- 5 cc/cc and shows the consistency in bulk scale synthesis of COFs. The cyclic equilibrium CH4 adsorption studies showed the COFs are stable with consistent CH4 adsorption and desorption cycles. The present study is a step towards the scalable mechanochemical synthesis of COFs for gas storage applications.
Keywords: CH4 storage; COF; porous material; scalable synthesis

Scalable approach using a gC3N4 -covalent organic framework hybrid catalyst towards sustainable hydrogen production from seawater and wastewater - Asokan, Kiran; Bhagyasree, T. M.; Devasia, George; Krishnamurty, Sailaja; Solim, Sabah; Rueda, Lina; Al-Mohannadi, Dhabia M.; Al-Hashimi, Mohammed; Kakosimos, Konstantinos; Santhosh Babu, Sukumaran (CHEMICAL SCIENCE, 2024)